Assessing the endothelium’s role in COVID-19 severity using the HUVEC model - Santana, Sanzio Silva; Yahouédéhou, Sètondji Cocou Modeste Alexandre; Adanho, Corynne Stéphanie Ahouéfa; Silva, Jéssica Rebouças; Santos, Hayna Malta; Barbosa, Cynara Gomes; Pitanga, Thassila Nogueira; Borges, Valéria Matos; Fortuna, Vitor; Lyra, Isa Menezes; Goncalves, Marilda Souza (Frontiers in Immunology, 2026)
IntroductionCoronavirus disease 2019 (COVID-19) has been widely associated with intense systemic inflammation, endothelial injury, and a high incidence of thrombotic complications, which together contribute to disease severity and poor clinical outcomes. While endothelial dysfunction, dysregulated cytokine production, and oxidative stress are recognized features of severe COVID-19, the direct impact of circulating factors from infected individuals on endothelial cell behavior remains insufficiently characterized. Here, we examined how serum from patients with severe COVID-19 and from convalescent individuals modulates endothelial activation, inflammatory responses, and oxidative stress using human umbilical vein endothelial cells as an in vitro model.MethodsVenous blood samples were collected from individuals with severe COVID-19 (n = 13), convalescent patients (n = 11), and healthy volunteers (n = 7) during the initial phase of the COVID-19 pandemic. Human umbilical vein endothelial cells (HUVEC) were maintained in culture and exposed to 15% serum from each study group after a period of serum deprivation. The expression of genes associated with endothelial activation, thrombosis, inflammation, and oxidative stress was analyzed by quantitative real-time PCR at defined time points. In addition, the endothelial secretory profile was evaluated in cell culture supernatants using multiplex bead-based immunoassays. Statistical analyses were performed using one-way ANOVA followed by appropriate post hoc tests, receiver operating characteristic (ROC) curve analysis to assess the discriminatory capacity of biomarkers, and multivariate linear regression to identify factors associated with disease severity.Results and discussionWe investigated the role of the endothelium in modulating the cytokine storm in severe COVID-19. HUVEC were stimulated with serum from patients with severe COVID-19, convalescent individuals, and healthy volunteers. Stimulation with serum from severe cases induces significant increases in VCAM1, F3, PROCR, IL6, IL12A, NFE2L2, HMOX1, GPX1, and GSR expression within 60 minutes. Antioxidant genes SOD1 and CAT were upregulated later, after 120 minutes. HUVEC stimulated with severe COVID-19 sera showed increased levels of sICAM-1, sVCAM-1, P-selectin, sE-selectin, PECAM-1, tissue factor, thrombomodulin, and a broad range of cytokines and growth factors, such as IL-1α, IL-1Ra, IL-5, IL-6, IL-10, IL-12(p40), IL-18, IL-27, TNF-α, TGF-α, FGF-2, G-CSF, M-CSF, FLT-3L, fractalkine, eotaxin, MIG, IP-10, MIP-1β, MDC, GROa and PDGF-AB/BB. In contrast, convalescent sera induced fewer markers, specifically IL-12(p40), IL-18, FGF-2, MIP-1β, MDC, GROa, and PDGF-AB/BB, while HV sera induced significant increases in IL-12(p40), IL-27, TNF-α, VEGF, MDC, eotaxin, and GROa. ROC curve analysis revealed that P-selectin and MIP-1β levels clearly distinguish severe cases from HV. When comparing severe and convalescent groups, we observed increases in IL-27, TGF-α, sVCAM-1, IL-1α, and G-CSF levels. Furthermore, Multivariable logistic regression analysis associated disease severity with decreased IL-10 and increased MIP-1β, sICAM-1, and P-selectin.ConclusionThese findings suggest that HUVEC serves as a promising biological sensor for detecting inflammatory responses in COVID-19 patients and shows the crucial role of the endothelium in sustaining the cytokine storm that contributes to patient severity and mortality.